조도 변화에 따른 뇌파 기반 생체신호 변화에 관한 연구 - 김명호(Myung Ho Kim) (전기학회 논문지 P권, 61(1), 2012)
By using EEG and HRV, subjects were estimated on their psychological and physiological reaction when reading psychrometric chart in 7 point century font, in an environmental test room in the condition of temperature 25[$^{\circ}C$], relative humidity 50[RH%], air current speed 0.02[m/sec], giving variation in illuminance to 0.1, 300, 600, 1000, 1300 and 1600[lux]. As a result, it was at 1300[lux] that absolute ${\alpha}$ wave, SMR, SDNN were most vitalized, and also both sides ${\alpha}$ wave asymmetry index, SEF50, HRT, stress and fatigue degree were at the lowest. It was found that a certain illuminance which minimizes psychological stress and fatigue degree while enhancing concentration and task achievement stably does exist.